2017
DOI: 10.1111/ecc.12715
|View full text |Cite
|
Sign up to set email alerts
|

Patient characteristics and surgery-related factors associated with patient-reported recovery at 1 and 6 months after colorectal cancer surgery

Abstract: Predictors for postoperative recovery after colorectal cancer surgery are usually investigated in relation to length of stay (LoS), readmission, or 30-day morbidity. This study describes patient characteristics and surgery-related factors associated with patient-reported recovery 1 and 6 months after surgery. In total, 153 consecutively included patients who were recovering from colorectal cancer surgery reported their level of recovery using the Postoperative Recovery Profile. Multiple logistic regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 34 publications
0
25
0
1
Order By: Relevance
“…Higher cortisol levels and lower NK-cell activity in DC from 7 to 9 days after surgery to discharge than CC might entail insulin resistance, hyperglycemia, and immune dysfunction, increasing the risk of infection, and leading to worse quality of recovery. 5 , 19 , 43…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher cortisol levels and lower NK-cell activity in DC from 7 to 9 days after surgery to discharge than CC might entail insulin resistance, hyperglycemia, and immune dysfunction, increasing the risk of infection, and leading to worse quality of recovery. 5 , 19 , 43…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 , 4 Few studies have found that perioperative stress could aggravate postoperative physical impairment (eg, pain and fatigue), increase the risk of postoperative complications, and delay patients' postoperative recovery. 3 , 5 , 6 Beyond in-hospital recovery, there is emerging evidence that surgery-related psychological stress may also potentially trigger tumor dissemination. 3 , 7 Given the potential adverse effects of psychological stress, there is a need to pay more attention to managing patients’ psychological stress during the short perioperative timeframe to maintain the mental health of gastrointestinal cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…One strength of this study is its use of the validated PSR13 for confirming established predictors of postdischarge surgical recovery in both an expected and unexpected direction. Medical co-morbidities (67) and perioperative complications (6), (810), were negatively associated with postdischarge surgical recovery, beginning early in its trajectory in the expected direction. The ability to reduce the severity of prolapse with reconstructive surgery translated into better postdischarge surgical recovery as expected, at 42 to 90 days likely mediated by a “return to normalcy” once the negative impact of medical co-morbidities and perioperative complications ran their course.…”
Section: Discussionmentioning
confidence: 99%
“…Unresponsive statements such as “it depends”, or “I am not sure” are largely based on observations that recovery time varies widely among patients undergoing similar surgeries (3), (4), and (5). Sociodemographic/clinical and surgical predictors including age (6), (7), (8), body mass index (7), (9), medical co-morbidities (6), (7), and surgical complications (6), (8), (9), (10) have been found to be important predictors of recovery from a variety of surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…It contains elements in the dimensions of symptoms, function, psychological, social and activity. This instrument identified several factors that seemed to be related to poorer recovery, and patients with these issues may benefit from individualized follow-up routines during the recovery period [88].…”
Section: Post-operative Assessmentsmentioning
confidence: 99%